2000
DOI: 10.1038/sj.onc.1203402
|View full text |Cite
|
Sign up to set email alerts
|

Positive regulation of skeletal myogenesis by R-Ras

Abstract: Most of the proteins in the Ras-family proteins, including Ras, Rap and TC21, have been reported to be strong inhibitors of skeletal myogenesis. Here we show that R-Ras, another member of this family, promotes terminal dierentiation of C2C12 skeletal myoblasts. In contrast to Ras, which induced a markedly transformed phenotype of C2C12 cells, an activated mutant of R-Ras (R-Ras Q87L ) did not exhibit any inhibitory eect on the dierentiation of C2C12 cells, but enhanced the formation of multinucleated myotubes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…R-Ras is known to induce haptotaxis in breast epithelia and skeletal myoblasts (Keely et al, 1999;Holly et al, 2000;Suzuki et al, 2000). We extend this observation further by showing that Q87L R-Ras potentiates chemokinesis or random cell movement driven by the presence of serum.…”
Section: Regulation Of Cell Migration By R-rassupporting
confidence: 60%
See 1 more Smart Citation
“…R-Ras is known to induce haptotaxis in breast epithelia and skeletal myoblasts (Keely et al, 1999;Holly et al, 2000;Suzuki et al, 2000). We extend this observation further by showing that Q87L R-Ras potentiates chemokinesis or random cell movement driven by the presence of serum.…”
Section: Regulation Of Cell Migration By R-rassupporting
confidence: 60%
“…These authors also showed that R-Ras increased the affinity of the prototype platelet integrin, ␣IIb␤3, for soluble ligand, suggesting that R-Ras regulates integrins through an "inside-out" signaling mechanism. R-Ras has also been implicated in cell spreading (Berrier et al, 2000), cell survival (Suzuki et al, 1997;Osada et al, 1999) and haptotactic migration (Keely et al, 1999;Suzuki et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Other groups described opposite results, since treatment with PD restored di erentiation of infected Raf embryonic chick myoblasts (Dorman and Johnson, 1999). Moreover, other Ras isoforms, such as R-Ras, resulted in positive regulation of skeletal myogenesis (Suzuki et al, 2000).…”
Section: Introductionmentioning
confidence: 92%
“…Activated versions of R-Ras3 transform NIH 3T3 fibroblasts and induce neurite outgrowth in PC12 cells (16,31,32). R-Ras can transform some, but not other, cell types (12,39,61) and also has functions clearly different from those of Ras (62,70,78). Rap1 proteins, although originally proposed to act by antagonizing Ras function, have functions that are different from those of Ras, some of which may involve the regulation of integrin-mediated adhesion (6).…”
mentioning
confidence: 99%